About the performance of Sphaerotilus natans to reduce hexavalent chromium in batch and continuous reactors - Caravelli, Alejandro Horacio (2009)
The hexavalent chromium biological reduction constitutes a safe and economical detoxification procedure of wastewaters containing Cr(VI). However, little research has been done to evaluate Cr(VI) tolerance and reduction capacity of microbial cultures under different growth conditions. The aims of this work were (a) to evaluate the capacity of Sphaerotilus natans to reduce Cr(VI) to Cr(III) in a continuous system limited in carbon and energy source or in nitrogen source, (b) to evaluate the toxic effect of Cr(VI) on this microorganism, (c) to carry out a complete analysis of Cr(VI) reduction by S. natans not only in continuous regime but also in batch system, and (d) to model the obtained results mathematically. S. natans exhibited great resistance to Cr(VI) (19 - 78 mg l-1) and optimal growth in continuous and batch systems using a mineral medium supplemented only with citric acid as organic substrate. In carbon- and energy-limited continuous systems, a maximum percentual decrease in Cr(VI) by 13%was reached for lowinfluent Cr(VI)concentration (4.3 - 5.32 mg Cr (VI) l-1); the efficiency of the process did not notoriously increase as the length of cellular residence timewas increased from 4.16 to 50 h. A nitrogen-limited continuous operation with a cellular residence time of 28.5 h resulted in a Cr(VI) decrease of approximately 26 – 32%. In batch system, a mathematical model allowed to predict the Cr(VI) concentration as a function of time and the ratio between the initial Cr(VI) concentration and that of the biomass. High concentrations of initial Cr(VI) and biomass produced the highest performance of the process of Cr(VI) reduction reached in batch system, aspects which should be considered in detoxification strategies of wastewaters.